Daya Serap Lembaga-Lembaga Fatwa di Indonesia Terhadap Masalah Hukum Kontemporer - Ajub Ishak (LP2M Institut Agama Islam Negeri Sultan Amai Gorontalo, 2015)
This paper discusses the existence of the fatwa institutions in Indonesia to solve the problems of contemporary law. This is evident in the implementation of Islamic law are represented by several institutions fatwas, such as the Indonesian Ulema Council (MUI), which has a Fatwa Commission; Muhammadiyah has Majlis Legal Affairs Committee, Nadhatul Ulama (NU) has Bahtsul Masa'il, and Persatuan Islam (Persis) has Hisbah Board, and the Ministry of Health of the Republic of Indonesia has a Health Advisory Council and Syara (MPKS). This paper is a literature study using fiqh approach and sociology of Islamic law approach. The results showed the existence of the fatwa is crucial to answering the legal status of contemporary issues in society. But the results fatwa has no consequences and legal consequences for all the strict Muslim society.